Genome-Wide Identification, Evolutionary Expansion, and Expression Analyses of Aux/IAA Gene Family in Castanea mollissima During Seed Kernel Development - Yujuan Tian; Jingmiao Huang; Jinxin Wang; Dongsheng Wang; Ruimin Huang; Xia Liu; Haie Zhang; Jingzheng Zhang; Xiangyu Wang; Liyang Yu (Biology, 2025)
Auxin/induced-3-acetic acid (Aux/IAA) serves as a key regulator in the auxin signaling pathway of plants, which exhibits crucial functions in the development of plants. However, the Aux/IAA gene family has not yet been characterized in the genome of Castanea mollissima, an important food source in the Northern Hemisphere. During this research, 23 Aux/IAA genes were identified in the C. mollissima genome, which were unevenly distributed across seven chromosomes. CmAux/IAA genes were assigned to four subfamilies by phylogenetic analysis, and members of the same subfamily exhibited similar molecular characteristics. Collinear analysis revealed that the expansion of CmAux/IAA genes was primarily driven by whole-genome duplication (WGD) and purifying selection. The promoter regions of CmAux/IAA genes were enriched with development-related and hormone-related cis-acting elements, suggesting their crucial functions in the growth and hormonal regulation of C. mollissima. Upon the maturation of the seed kernels, the size and starch content exhibited a significant increasing trend, alongside notable changes in hormone levels. Given the connections between expression levels and physiological indicators, as well as weighted gene co-expression network analysis (WGCNA) analysis, CmIAA27a, CmIAA27b, and CmIAA27c were identified as potential regulators involved in the development of C. mollissima seed kernels. Furthermore, the reliability of the transcriptomic data was further confirmed by RT-qPCR experiments. Overall, this study provides a theoretical basis for the evolutionary expansion of the Aux/IAA gene family in C. mollissima, alongside its potential functions in seed kernel development.